Situation Report: Romania, 30 October 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reassignment of Specialists (III) Manescu to Prague North Vietnamese Economic Delegation in Romania Criticism of Centralization in Writers' Union World Marxist Reader Editorial Committee Meets International Bank Chairman Arrives in Bucharest Reaction to Brandt Policy Statement Birth Rate Decreasing Agerpres on Romania's Eastern Trade in 1969